Remote Learning in the Crisis of Covid-19: Motivating or Demotivating the EFL Students to Learn? - Sumarsono, Dedi; Suadiyatno, Taufik; Bagis, Abdul Kadir (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2022)
The implementation of virtual learning in the time of covid-19 pandemic had potentially affected the studentsâ€™ learning motivation. This research was aimed at finding out; (1) the level of the EFL learning motivation when the remote learning is implemented during the Covid-19; (2) How was the EFL learning motivation when the remote learning implemented during the Covid-19. This study was conducted at two different universities majoring English department and medical laboratory technology department consisting of 202 students. To gain the data, a questionnaire on learning motivation was delivered to the students. The data was analyzed using the Likert scale of agreement or disagreement to interpret the types of learning English motivation. In analyzing the data, both quantitative and qualitative were used as a mixed-methods was applied. The findings of the study showed that the students’ motivation was categorized into high level or slightly close to medium level of motivation. Other interesting findings were that the distance learning was claimed less effective because the materials were claimed tent to be difficult, error internet connection, less interaction between students and teachers, and so forth. On the other hand, some students argued that digital learning improves their ability in utilizing the technology media, encourages, encouraged them to be independency and curiosity, and trained the students to be more confident.